Pengaruh Kontribusi Pajak Bumi dan Bangunan Perdesaan dan Perkotaan dan Bea Perolehan Hak atas Tanah dan Bangunan terhadap Pajak Daerah di Kota Bandung - Tika Sundari; Arif Afriady; Arry Irawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Land and Building Taxes for Rural and Urban Areas and Fees on the Acquisition of Land and Building Rights are the two local taxes in Bandung City with the highest realization, but these potentials have not been managed properly so that they become the largest source of regional receivables in Bandung City since they have not reached the target. This study aims to determine the effect of Land and Building Taxes for Rural and Urban Areas and Fees on the Acquisition of Land and Building Rights Contribution toward Local Taxes in Bandung City, either partially or simultaneously. This type of research is a quantitative method using a sample of 60 months starting from January 2016 to December 2020. The data used is documentary data and analyzed using multiple linear regression analysis. The results of this study indicate that the contribution of Land and Building Taxes for Rural and Urban Areas and Fees on the Acquisition of Land and Building Rights has a significant effect either partially or simultaneously on Local Taxes in Bandung City. As much as 71,5% of Local Taxes is influenced by the contribution of Land and Building Taxes for Rural and Urban Areas and Fees on the Acquisition of Land and Building Rights while the rest is influenced by other factors.